A história da laranjinha: uma proposta de livro infantil sobre frutas - Coelho, Mariana Silva (Universidade Federal de São Carlos, 2020)
Botany is an area of science that started very early in human history. It developed over the early centuries, but in the last few decades it holds one of the most boring methods of teaching Education. This scenario makes the socialization process between human beings and plants something basically impractical outside the classroom, which makes the process of assimilation and appreciation of the presence of vegetables in people's daily lives very difficult, which we call Plant Blindness. In Basic Education, the situation of Botany is not favorable given that there are almost no mentions of plants in the National Common Base Curriculum for this phase. Therefore, we thought of a proposal to bridge the gap between the teaching of Botany and Early Childhood Education, in the form of a children's story book, entitled “The story of the little orange”. The book was produced to help the teacher to start introducing the subject in a more playful way for children of 3 to 4 years-old. Therefore, this material was designed with the hope that it will contribute to the future of these children and the plants that surrounds us. The main objective was arousing children's curiosity for the plants that surround them and acting in scientific dissemination. The story was told to some students at a Childhood Education Center in the city of Sorocaba, in the state of São Paulo. With the results obtained, we were able to confirm that there are many gaps between the teaching of Botany and Early Childhood Education.
The story of the little orange: a children's book proposal about fruits
Keywords: Cegueira botânica; Educação infantil; Livro infantil; Contação de história; Material didático; Divulgação científica; Desenvolvimento e morfologia; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM